Eugenia kuhlmanniana (Myrtaceae), a new synonym of E. hiraeifolia, a Mesoamerican species cultivated in Brazil - Mazine, Fiorella; Faria Jr., Jair Eustáquio Quintino; Souza, Marcelo Costa; Lucas, Eve (Phytotaxa, 2015)
The synonymization of Eugenia kuhlmanniana Mattos & D. Legrand, previously described as endemic from Rio de Janeiro, Brazil, under Eugenia hiraeifolia Standley is proposed.